Pengaruh Profitability Dan Institutional Ownership Terhadap Income Smoothing Dengan Moderasi Firm Size - Meita Florentina; Rini Tri Hastuti (Jurnal Ekonomi, 2022)
The purpose of this study is to determine the effect of profitability and institutional ownership towards income smoothing practice with firm size as moderating variable in manufacturing companies listed in the Indonesia Stock Exchange from the period 2018 – 2020. This study used 72 data from manufacturing companies that have been selected using the purposive sampling method with a total of 216 data for three years. The data used are secondary data in the form of financial statements. This research used econometric views (EViews) version 12 software to process the data. The result of the research shows that return on assets has no significant effect and institutional ownership has a positive significant effect on income smoothing practice. Firm size has no significant effect on the relation of return on asset and income smoothing practice, and firm size has no significant influence on the relation of institutional ownership and income smoothing practice.